The level of quality teaching in private institutions: comparative study based on students' perceptions and expectations. (2017) - Al-Hemyari, Zuhair A.; Al-Humairi, Ali
Investigating and utilising the feedback, academic staff opinions and students' perceptions on teaching and learning will impact the quality of teaching and play an important role in expanding the reputation of institutions. One of the main purposes of this article is to highlight the importance of students' opinions in institutions through reviewing several aims and plans of educational bodies of Oman. In particular, the paper reviews two national studies on students' perceptions and expectations of the quality of teaching in private institutions: the methodologies of the two studies were discussed and the paper gave useful and simple comparisons between them. The paper determines ten common indicators between the studies - the results of the indicators are tested and compared and in general they are only average and approximately equal. The conclusions are clarified and the limitations of both studies are discussed in order to improve the future studies on quality teaching.